Transplantes: re-inserção social e qualidade de vida dos transplantados cardíacos do Estado do RN - Cesana, Sarita (2008)
The experience of transplantation is a very serious situation from the clinical standpoint. Therefore, there must be some subjective and social breakdown in people who have been undergone such a procedure. Recent product of modernity, the transplanted is someone who owns his recover to the scientific advances of contemporary society and a deceased donor. This paper aims at examine the implications, from the changes in patterns of behavior and thought that occur after the experience of an extreme and critical situation, as the process of illness and its consequent transplant surgery. The symbolism of the heart suggests that some social impressions about the organ itself are also reflected in how the transplanted interprets the experience of this type of procedure. So investigating how the changes occurred throughout the process interfere in the re-insertion of these people to social life, after his recovery, is the purpose of this work. The concept of habitus coined by Pierre Bourdieu will be used to measure conceptually how this experience (clinical, modern and symbolic) fits in the contemporary discussion of sociology